More Natural Does Not Equal More Normal: Lesbian, Gay, and Bisexual People's Views About Different Pathways to Parenthood. (December 2018) - Pralat, Robert
Heterosexual reproduction is often seen as normal and natural, with the two descriptors commonly understood as mutually reinforcing. I argue that, despite their apparent similarity, the meanings of "normal" and "natural" are distinct in important ways—a distinction that questions the positioning of lesbian motherhood and gay fatherhood as inferior. Through an analysis of lesbian, gay, and bisexual people's ethical judgments about different ways of creating families, I show that pathways to parenthood that make a family appear "more normal" rely on means of reproduction that seem, in fact, "less natural." Conversely, reproductive possibilities seen as "more organic" create families that depart more substantially from the cultural norm of the nuclear family. As a result of this tension, different pathways to parenthood can be justified as being "in children's best interests." However, while this children-centered justification can be flexibly applied, it also has contradictory meanings.